EXAMINING THE RELATIONSHIP BETWEEN NATURAL RESOURCE WEALTH AND ECONOMIC GROWTH: EMPIRICAL EVIDENCE FROM THE UNITED STATES (Third Sector Social Economic Review, 2023)
After the 1980s, it is seen that there is little consensus about the effect of countries having rich natural resources on economic growth and the mechanism underlying this effect. In this context, many theoretical relations are discussed in the literature in order to direct the potential impact path of natural resources to economic growth. One of the striking results is that resource-rich countries have slower economic growth rates than resource-poor countries. In this context, the aim of this research is to examine the short and long term connections between natural resource components and growth in of the United States in the 1990-2020 period, based on the resource curse and environmental economic growth model. While the long term coefficient findings of the cointegration methodology indicate that the variables of GDP and capital, labor force, forest areas, electricity production from non-renewable resources, arable and agricultural areas are positive; schooling, natural resource rents and cultivated areas variables show that they are negative. As the short term coefficient findings indicate that the variables of GDP and capital, labor, electricity production from non-renewable resources and agricultural areas are positive; schooling, natural resource rents and cultivated areas variables indicate that they are negative. However, long and short term findings explain that the resource curse hypothesis is confirmed by the fact that natural resource rents restrict economic growth. At the same time, capital formation and labor support economic performance.
Keywords: Natural resources; environment; economic growth; resource curse hypothesis; ARDL cointegration approach